Sharia Pawnshop Strategy in Improving Financial Literacy in the Mandailing Natal Community - Rista Mardatilla; Azwar Hamid; Samsuddin Muhammad (Al-Hiwalah: Journal of Sharia Economic Law, 2025)
This study discusses how the actual strategy carried out by Islamic pawnshops in increasing financial literacy of the community both directly and indirectly, Islamic pawnshops are also one of the (IKNBS) which have an important role in socializing the importance of Islamic economics in the midst of Muslim society. So the purpose of this study is to find out how important financial literacy is in the community and the strategies carried out by Islamic pawnshops in increasing financial literacy of the Mandailing Natal community. This research method uses qualitative research, the data sources used are primary data and secondary data, the data collection techniques are by conducting observations, interviews and documentation, the data analysis techniques carried out are by conducting data reduction, data presentation and conclusions. The results of this study indicate that Islamic financial literacy at UPS Pegadaian Syariah Mandailing Natal has a good understanding of the principles of Islamic finance which is very important for the community, especially Muslims. Then Pegadaian UPS Pegadaian Syariah Mandailing Natal has successfully implemented various strategies to improve sharia financial literacy in the community since its establishment in 2015. With government support and compliance with the regulations of the Financial Services Authority (OJK), the literacy programs they run target various community groups such as entrepreneurs, private employees, civil servants, and the general public.